The Private Higher Education Regulation in Ethiopia: Jurisprudence and Practices - Disassa, Desalegn (Hasanuddin Journal of International Affairs, 2025)
Well-regulated education is a powerful weapon for positive social change. Ethiopia formally allowed private actors to join the education industry in 2003. Since then private higher education institutions have grown in number and enrolling capacity. This is a huge success in ensuring access to higher education to support country development through the provision of skilled manpower. However, because of weak regulation, there is a claim that private higher education institutions are working as a degree mill which negatively impacts the quality and relevancy of higher education. Having this in mind, this article examines the effectiveness of government regulation of private higher education institutions during the entry, operation and exit stages. To this end, relevant laws and policies, reports, government decisions, and literature are critically examined sideline with primary data collected through case studies and direct observation of private higher education institutions. As the findings of the study have revealed, despite the positive reform and development underway, the government regulation of private higher education institutions is ineffective and because of this, education which is recognized as a means of ruining social problems is ruined by bogus institutions and degrees. Mainly this problem is associated not with normative gaps; rather it is a result of weak enforcement as a result of the institutional weakness of relevant authority to efficiently undertake its mandate of licensing, accrediting, supervising, monitoring, and auditing. Besides, the government lacks a firm stand and strong commitment to take deterring measures against bogus institutions and graduates holding fake degrees. Based on the findings, the researcher called for strict enforcement of laws by strengthening the Authority with manpower and finance and adopting a holistic approach to fighting for the quality and relevancy of higher education.